Penerapan Matematika Dasar Pada Analisis Balok Sederhana Dalam Teknik Sipil - Hilkia Permatasari Zai (CV. SINAR HOWUHOWU, 2026)
Basic mathematics is a fundamental foundation in the field of Civil Engineering, especially in structural analysis. One of the most frequently analyzed structural elements is the simple beam, as it is widely used in buildings, bridges, and other civil structures. A simple beam functions to resist applied loads and safely transfer them to the supports.This paper aims to explain in a more detailed and easy-to-understand manner the application of basic mathematics in simple beam analysis. The mathematical concepts discussed include arithmetic, algebra, and trigonometry, which are applied in static equilibrium analysis, support reaction calculations, shear force determination, and bending moment analysis. The discussion is systematically arranged using original wording to help students understand the relationship between mathematical calculations and the physical behavior of beams under loading conditions.The method used in this paper is a literature study based on engineering textbooks and relevant standards, combined with conceptual analysis grounded in basic engineering mechanics principles. The results show that mastery of basic mathematics greatly influences the accuracy of structural analysis and serves as an essential foundation for Civil Engineering students in learning more advanced structural systems. With proper understanding, students are expected not only to perform calculations correctly but also to comprehend the engineering meaning behind the analysis results.